2015
DOI: 10.1007/s12205-015-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metakaolin on the chloride ingress properties of concrete

Abstract: Research and practical experience have shown that partial replacement of cement by metakaolin improves concrete durability as a result of the refinement of the pore structure. While much research has been presented on concrete performance with metakaolin, it is scarce concerning the transport properties of chlorides in concrete with metakaolin, in natural conditions (i.e., un-accelerated). This study determines the chloride diffusion coefficients for several concretes with vary levels of cement replacement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Table 1 lists the literature used in this study. Ferreira et al [16] Zhao [17] reported the derivative of pore size distribution and the intrusion steps were shown; however, each plot was not clear because there are many plots. Therefore, these were omitted in this study.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Table 1 lists the literature used in this study. Ferreira et al [16] Zhao [17] reported the derivative of pore size distribution and the intrusion steps were shown; however, each plot was not clear because there are many plots. Therefore, these were omitted in this study.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The colorimetric method of spraying silver nitrate is widely used in experimental works in which the tested concrete is found in saturation conditions and free from the carbonation process. Many works published in recent years in high-impact magazines (such as : Ferreira et al, 2016;Weiss et al, 2017;Wei et al, 2018;He et al, 2018;Slomka-Slupik et al, 2018;Fernández-Ruiz et al, 2018;Lau et al, 2018;Azarijafari et al, 2018) confirm its frequent use in current research. However, some studies (França, 2011;Real et al, 2015) point out that the silver ions (Ag+) in the silver nitrate solution react with the carbonation product CO3, forming Ag2CO3, which also gives a whitish color to the concrete.…”
Section: Relevance Of the Themementioning
confidence: 85%
“…The reaction products of metakaolin include calcium silicate hydrate (CSH), C 4 AH 13 , C 3 AH 6 , and C 2 ASH 8 [18]. Dunster et al [18] designed trimethylsilylation studies of the hydration of metakaolin-calcium hydroxide paste.…”
Section: Mk Reaction Modelmentioning
confidence: 99%
“…Güneyisi et al [4] and Wong [5] pointed out that the compressive strength was improved in MK blended concrete due to the pozzolanic reaction of MK. Ferreira et al [6] and Poon et al [7] stated that chloride diffusivity decreased as MK replacement levels increased. Ramezanianpour [8] and Duan et al [9] indicated that durability aspects, such as the resistances about sorptivity, water penetration, salt ponding, and carbonation, were improved due to MK additions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation